Rapid colour changes in Euglena sanguinea (Euglenophyceae) caused by internal lipid globule migration. Issue 1 (2nd January 2019) - Laza-Martínez, Aitor; Fernández-Marín, Beatriz; García-Plazaola, José Ignacio
ABSTRACT: The accumulation of red pigments, frequently carotenoids, under chronic stress is a response observed in diverse kinds of eukaryotic photoautotrophs. It is thought that red pigments protect the chlorophyll located underneath by a light-shielding mechanism. However, the synthesis or degradation of carotenoids is a slow process and this response is usually only observed when the stress is maintained over long periods of time. In contrast, rapid colour changes have been reported in the euglenophyte Euglena sanguinea . Here we study the ecophysiological process behind this phenomenon through chlorophyll fluorescence, and pigment, colour and ultrastructural analyses. Reddening in E. sanguinea was due to the presence of a large amount of free and esterified astaxanthin (representing 80% of the carotenoid pool). The process was highly dynamic, shifting from green to red in 8 min (and vice-versa in 20 min). This change was not due to de novo carotenogenesis, but to the relocation of cytoplasmic lipid globules where astaxanthin accumulates. Thus, red globules were observed to migrate from the centre of the cell to peripheral locations when exposed to high light. Globule migration seems to be so efficient that other classical photoprotective mechanisms are not operative in this species. Despite the presence and operation of the diadino-diatoxanthin cycle, non-photochemical quenching was almost undetectable. Since E. sanguinea forms extensive floating colonies, reddening can be observed at a much greater scale than at the cellular level and the mechanism described here is one of the fastest and most dramatic colour changes attributable to photosynthetic organisms at cell and landscape level. In conclusion E. sanguinea shows an extremely dynamic and efficient photoprotective mechanism, based more on organelle migration than on carotenoid biosynthesis, which prevents excess light absorption by chlorophylls reducing the need for other protective processes related to energy dissipation.